DISKURSUS CYBERBULLYING FLORENCE SIHOMBING (Analisis Wacana Kritis Teun A. Van Dijk Tentang Florence Sihombing di Dunia Maya) - Syntia Balina Dewi; Syarif Maulana (Program Studi Ilmu Komunikasi FBIK Unissula, 2015)
Cyberbullying is closely related to technology and social media. Dissemination of information via the Internet and social media is much faster than the oral way. Cyberbullying is often done through social media and headlines news portals, which make the reader interested in reading, usually used excessive sentences that can make someone cornered. This research study is entitled «Discourse Cyberbullying of Florence Sihombing (Critical Discourse Analysis Teun A. van Dijk about Florence Sihombing in Cyberspace)». The purpose of this study was to determine the discourse on cyberbullying in the case of Florence Sihombing based on critical discourse analysis Teun A. Van Dijk. The methodology used in this research is the analysis of discourse, in which the author collects screenshots of cyberbullyer tweets on Twitter and headlines on online news portals that are associated with the case of Florence Sihombing, then associated with critical discourse analysis van Dijk. The results of this study showed the cyberbullying that happened to Florence Sihombing through the online news headlines and cyberbullyer’s tweets on Twitter can be explained through nine elements contained in the critical discourse analysis of van Dijk.Keywords : cyberbullying, social media, news headline, Twitter’s tweets, critical discourse Teun A. Van Dijk